Development and validation of School Mental Skills Assessment Scale (SMSAS) - Oussama Bouiri; Said Lotfi; Mohammed Talbi (Образование и наука)
Introduction. Currently, the assessment of school mental skills is of practical interest. Aim. The present research aims to construct and validate a scale for assessing mental skills of schoolchildren. Methodology and research methods. The methodology was built using G. Churchill’s paradigm (1979) adapted to the tasks of the study, which included four stages: building a list of elements; analysing the accuracy of the SMS message scale; analysing inter-factor correlations; and analysing the validity of the scale. To test the methodology based on emotional, cognitive and metacognitive strategies on a voluntary basis, the authors distributed the scale to 311 actors in the Moroccan education system: students, teachers, inspectors and trainers. Results and scientific novelty. The findings indicated that by utilising exploratory factor analysis (EFA), the authors uncovered three distinct factors that compose the school mental competency evaluation scale, resulting in a score of 79.416%. Additionally, when evaluating semantic consistency, the KMO index exceeded the suggested threshold of 0.70. Finally, the assessment of “internal consistency” and “coherence” was exemplified by a notably elevated Cronbach’s alpha value of 0.848. Practical significance. The results obtained can be used as a tool for teachers and educationalists to assess school mental skills.